Is hospital care involved in inequalities in coronary heart disease mortality? Results from the French WHO-MONICA Project in men aged 30-64. Issue 10 (October 1998) - Lang, T; Ducimetière, P; Arveiler, D; Amouyel, P; Ferrières, J; Ruidavets, J B; Montaye, M; Haas, B; Bingham, A
Abstract : OBJECTIVES: The goal of the study was to assess whether possible disparities in coronary heart disease (CHD) management between occupational categories (OC) in men might be observed and contribute to the increasing inequalities in CHD morbidity and mortality reported in France. METHODS: The data from the three registers of the French MONICA Collaborative Centres (MCC-Lille, MCC-Strasbourg, and MCC-Toulouse) were analysed during two period: 1985-87 and 1989-91. Acute myocardial infarctions and coronary deaths concerning men, aged 30-64 years, were included. Non-professionally active and retired men were excluded. Results were adjusted for age and MCC, using a logistic regression analysis. RESULTS: 605 and 695 events were analysed for 1985-87 and 1989-91, respectively. Out of hospital cardiac arrests, with or without cardiac resuscitation, and 28 day case fatality rates were lower among upper executives in both periods. A coronarography before the acute event had been performed more frequently in men of this category and the proportion of events that could be hospitalised was higher among them. In both periods, the management of acute myocardial infarctions in hospital and prescriptions on discharge were similar among occupational categories. CONCLUSIONS: For patients who could be admitted to hospital, the management was found to be similar among OCs, as was the 28 day case fatality rate among the hospitalised patients. In contrast, lower prognosis and higher probability of being hospitalised after the event among some categories suggest that pre-hospital care and the patient's conditions before the event are the primary factors involved.